A PCR-mediated method for discrimination of Klebsiella oxytoca between closely related bacteria in environmental and clinical specimens - Kovtunovych, G.L.; Lytvynenko, T.L.; Negrutska, V.V.; Lar, O.V.; Koltukova, N.V; Kozyrovska, N.O. (Біополімери і клітина, 2003)
A specific detection method was developed to discriminate Klebsiella oxytoca between other species of the genus Klebsiella on the basis of PCR amplification of the unique DNA sequences within the polygalacturonase-encoding (pehX) gene. Four primers have been designed for performing PCRs gaining amplicons of 282, 344, 451 and 513 bp. The specificity of the test was verified by the lack of PCR products in case of related K. pneumoniae, K. planticola, and polygalacturonate-degrading species of the genus Erwinia. The PCR-mediated test gives a rapid answer, concerning the presence of K. oxytoca in a sample, or in differentiating this bacterium from other species, such as K. pneumoniae, with which they can be confused. The diagnostic test can be used in ecological monitoring of K. oxytoca as well as in medical laboratories. На основі ПЛР-ампліфікації унікальних послідовностей ДНК гена, що кодує фермент полігалактуроназу (pehX), розроблено специфічний метод для вирізнення бактерії K. oxytoca серед інших бактерій роду Klebsiella. Чотири пари праймерів створено для отримання ампліконів 282, 344, 451 та 513 п. н. Специфічність тесту підтверджено відсутністю продуктів ПЛР у близьких бактерій K. pneumoniae, K. planticola та видів роду Erwinia, що розкладають полігалактуронат ПЛР-тест дозволяє швидко визначити наявність K. oxytoca у зразку або відрізнити цю бактерію від представників інших видів, наприклад, від К. pneumoniae, яка дуже схожа на неї. Діагностичний тест може бути використано в екологічному моніторингу K. oxytoca, а також у медичних лабораторіях. На основе ПЦР-амплификации уникальних последовательностей ДНК гена, кодирующего фермент полигалактуроназу (pehX), разработан метод для выявления бактерии K. oxytoca среди других бактерий рода Klebsiella. Четыре пары праймеров созданы для получения ампликонов размером 282, 344, 451 и 513 пар нуклеотидов. Специфичность теста подтверждена отсутствием продуктов ПЦР у близких бактерий K. pneumoniae, K. planticola и видов рода Erwinia, разлагающих полигалактуронат ПЦР-тест позволяет быстро определить наличие К. oxytoca в образцах или отличить эту бактерию от представителей других видов, например, от K. pneumoniae, которая очень на нее похожа. Диагностический тест может быть использован в экологическом мониторинге K. oxytoca, а также в медицинских лабораториях.